“An excerpt from the letter [to D.]” by A.S. Pushkin: addressee, function, dating - Oleg Proskurin (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The article proves that the text, published in the literary almanac “Northern Flowers for 1826” under the title “An excerpt from A. Pushkin’s letter to D[elvig]”, was, in fact, created as a letter to Pushkin’s brother Leo (Lev Sergeevich). The article revises the date and pragmatics of this work, its connection with the literary and biographical context. The article contains a detailed critical analysis of the interpretations of the topic introduced by leading Pushkin scholars: Boris Modzalevsky, Mstislav Tsiavlovsky, Grigorii Vinokur, Vadim Vatsuro, Sergei Fomichev, and Yanina Levkovich. The conclusions of the author are based on a thorough study of the history of the text of the “letter”: its draft manuscript copy in the “Second Masonic notebook”, its fair copy, and all lifetime publications.